On the structure of the judicial class environmental assessments (Journal of actual problems of jurisprudence, 2018)
The investigation in the field of environmental offenses appointed judicial examination. The paper highlights those examinations, which are ranked as environmental. In the forensic literature of different views on the classification of environmental impact assessments. The authors propose a system of environmental impact assessments.Key words: environmental offenses, classification, legal environmental assessments, class, gender, structure.